Foreign currency loan conversions and currency mismatches. (April 2022) - Fischer, Andreas M.; Yeşin, Pınar
Highlights: We analyze the impact of loan conversion programs (LCPs) in Europe on systemic risk. We show that LCPs reduced financial stability risks linked to Swiss franc loans. But they heightened risks in other foreign currencies in individual countries. Euro mismatches remain a considerable risk to financial stability in those countries. Abstract: This paper examines the effect of currency conversion programs from Swiss franc-denominated loans to other currency loans on currency risk for banks in Central and Eastern Europe (CEE). Swiss franc mortgage loans proliferated in CEE countries prior to the financial crisis and contributed to the volume of non-performing loans as the Swiss franc strongly appreciated during the post-crisis period. Empirical findings suggest that Swiss franc loan conversion programs reduced currency mismatches in Swiss francs but increased currency mismatches in other foreign currencies in individual countries. This asymmetric effect of conversion programs arises from the loan restructuring from Swiss francs to a non-local currency and the existing high level of euro mismatches in the CEE banking system.